2011
DOI: 10.1007/s10531-011-0114-0
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of land-use on West African savanna vegetation: a comparison between protected and communal area in Burkina Faso

Abstract: Biodiversity matters in many aspects for human well-being by providing timber and non-timber products. The most important ecosystems providing these products in West Africa are savannas. In the context of land-use changes, there is an urgent need to understand the impact of land-use on savanna vegetation and biodiversity. This study assesses the impact of land-use on savannas by comparing protected and communal areas. Vegetation relevés were performed in the W National Park and its surrounding communal area in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 41 publications
(44 reference statements)
6
57
0
9
Order By: Relevance
“…Cette superficie a été retenue en référence à des travaux antérieurs dans la zone soudanienne (NACOULMA et al, 2011). Par contre, dans les champs, cette surface était de 2 500 m² conformément aux travaux d 'AUGUSSEAU et al (2005), menés sur la biodiversité des arbres dans les agrosystèmes du Sud-Ouest du Burkina Faso.…”
Section: B O I S E T F O R ê T S D E S T R O P I Q U E Sunclassified
See 2 more Smart Citations
“…Cette superficie a été retenue en référence à des travaux antérieurs dans la zone soudanienne (NACOULMA et al, 2011). Par contre, dans les champs, cette surface était de 2 500 m² conformément aux travaux d 'AUGUSSEAU et al (2005), menés sur la biodiversité des arbres dans les agrosystèmes du Sud-Ouest du Burkina Faso.…”
Section: B O I S E T F O R ê T S D E S T R O P I Q U E Sunclassified
“…Par contre, cette équirépartition des individus des différentes espèces dans les formations anthropisées serait liée à l'impact agricole. En effet, sur les espaces agricoles, le système de culture basé sur la rotation jachère-culture et la pratique de l'agroforesterie favorisent le maintien des espèces utiles avec des proportions presque similaires, notamment celles à fruits comestibles comme Vitellaria pardoxa, Parkia biglobosa, Lannea microcarpa, Diospyros mespiliformis (DEVINEAU, 2010 ;NACOULMA et al, 2011). Par ailleurs, l'adaptation de certains arbustes tels que Combretum glutinosum, Piliostigma reticulatum et Piliostigma thonningii aux cycles culturaux favorise également leur maintien dans les espaces soumis à l'agriculture (NACOULMA et al, 2011).…”
Section: Diversité Ligneuse Et Mode D'utilisation Des Terresunclassified
See 1 more Smart Citation
“…Many studies have previously been conducted on some of the identified priority species in Africa such as P. erinaceus (Ouédraogo et al, 2006;Nacoulma et al, 2011;Segla et al, 2016), A. africana and K. senegalensis (Gaoué et al, 2007;Traoré et al, 2011;Delvaux et al, 2009). All these studies have assessed population variations across ecological regions, the impact on population structure under different land use systems, viability of these species and proposed conservation strategies for their sustainable management and finally targeted sensitization of populations around habitats where the species occur to ensure conservation of these highly valued species.…”
Section: Discussionmentioning
confidence: 99%
“…Mais aujourd'hui sous l'effet conjugué de la démographie galopante et les besoins de terres cultivables, les galeries forestières sont prises d'assaut par les paysans et elles sont soumises aux systèmes traditionnels d'utilisations des terres qui se résument en la culture itinérante sur brulis, le pâturage extensif de bétail, la collecte de bois de feu, la production de charbon de bois, l'exploitation forestière commerciale, la récolte de produits forestiers non ligneux et les établissements humains (Orékan, 2007;. Nacoulma et al, 2012). Ce système traditionnel d'utilisation des terres a abouti à la fragmentation des forêts galeries ce qui induit la perte immense de la diversité biologique tant végétale qu'animale.…”
Section: Introductionunclassified